Language and Cultural Peculiarities of Gender Realisation - Voloshina, Tatiana; Qi, Wang; Slobodova Novakova, Katarina; Baghana, Jerome; Pavlikova, Martina (Journal of Education Culture and Society, 2022)
Aim. The aim of the article is to reveal gender realisation peculiarities in English and German advertising texts. The concept of the research work is focused on the idea that representatives of different languages and cultures make unique world environment. The work proves the concept validity of the unique language nature in the distinctive idea of its cognitive base formed by an ethnic group. Methods. The concepts of universality and uniqueness of the linguistic and cultural features of gender perception are revealed using the methods of analysis and generalisation. Results. The result of the research work is in the necessity for advertising texts to have special gender language markers which are the kind of signal influencing the conscience of men and women while making purchases. The authors stress that social characteristics of men and women, such as age, social or family status expressed in the form of various degrees of comparison of adjectives are used mainly in English magazines; while German advertising texts put the use of adjectives and articles on the first place. Advertising for women have the set of a special expressive and emotional language tools complex while for men the use of vocabulary stressing the main type of activity of a man - energy is of the top priority. Conclusion. The research work presents cognitive value in theory and practical recommendations to gender linguistics specialising in advertising texts structure illustrating peculiar features of men and women as consumers being influenced by language, cultural, psychological characteristics.